2021
DOI: 10.1002/slct.202100553
|View full text |Cite
|
Sign up to set email alerts
|

Cu(OH)2 Nanorods/Ni(OH)2 Nanosheets as Highly Efficient Catalyst for Hydrogen Evolution Reaction

Abstract: Reasonably designing the catalyst in-situ grown on conductive substrate is a promising avenue to ameliorate the hydrogen evolution reaction (HER). In this work, we fabricated Cu(OH) 2 nanorods (NRs) and Ni(OH) 2 nanosheets (NSs) on single crystal Cu foil for the first time. The structure and morphology of all samples were systematically investigated by XRD and SEM, respectively. XPS was carried out to measure the element composition and valence state. The synergistic effect of metal double hydroxides significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been reported that Cu(OH) 2 could behave as active sites to promote the HER. 50 The newly formed active site, i.e., Cu(OH) 2 offsets the disappearance of the original active sites, i.e., CoS on the sample surfaces; therefore, the electrode activity did not undergo a significant attenuation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Cu(OH) 2 could behave as active sites to promote the HER. 50 The newly formed active site, i.e., Cu(OH) 2 offsets the disappearance of the original active sites, i.e., CoS on the sample surfaces; therefore, the electrode activity did not undergo a significant attenuation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Cu(OH) 2 could behave as active sites to promote the HER. 50 The newly formed active site, i.e. , Cu(OH) 2 offsets the disappearance of the original active sites, i.e.…”
Section: Resultsmentioning
confidence: 99%